2017
DOI: 10.1016/j.fertnstert.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of predictive models for polycystic ovary syndrome using serum levels of two antimüllerian hormone isoforms (proAMH and AMHN,C)

Abstract: The proAMH and AMH do not appear to improve the ability to predict a diagnosis of PCOS beyond total AMH assays. However, the ratio of inactive proAMH precursor to receptor-competent AMH (API) differs in women with PCOS relative to unaffected controls indicating that AMH signaling mechanisms may be altered in women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
(56 reference statements)
1
5
1
Order By: Relevance
“…Our findings indicate that, regardless of PCOS, the relative distribution of inactive AMH to active AMH is associated with metabolic parameters. Increased BMI, waist circumference, C-peptide, low-density lipoprotein cholesterol and triglycerides, and decreased high-density lipoprotein cholesterol, SHBG, and modified HOMA were associated with a lower ratio of uncleaved (inactive) AMH to cleaved (active) AMH in the present study, which is in line with the findings in the Pankhurst et al study (9). Some studies have found lower levels of total AMH in obese PCOS women (19), whereas others have found no correlation between AMH and BMI (20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings indicate that, regardless of PCOS, the relative distribution of inactive AMH to active AMH is associated with metabolic parameters. Increased BMI, waist circumference, C-peptide, low-density lipoprotein cholesterol and triglycerides, and decreased high-density lipoprotein cholesterol, SHBG, and modified HOMA were associated with a lower ratio of uncleaved (inactive) AMH to cleaved (active) AMH in the present study, which is in line with the findings in the Pankhurst et al study (9). Some studies have found lower levels of total AMH in obese PCOS women (19), whereas others have found no correlation between AMH and BMI (20).…”
Section: Discussionsupporting
confidence: 93%
“…The ratios of the AMH isoforms did not differ between PCOS and control subjects, meaning that the relative distribution of inactive (uncleaved) AMH and active (cleaved) AMH were the same in PCOS and control subjects. In contrast, Pankhurst et al (9) found that the ratio between pro-AMH (inactive) and receptor-competent AMH was decreased in PCOS women, indicating a higher conversion of non-receptor-competent AMH to receptor-competent AMH in women with PCOS; however, that study involved a limited number of patients. The AMH isoforms tested in the Pankhurst et al study were not similar to the ones tested in the present study, and furthermore the study subjects were not matched by age and BMI and the women with PCOS were significantly younger than the control women and had significantly higher BMI, waist circumference, and HOMA insulin resistance.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, there is a lack of data on clustering of AMH levels with other PCOS features and relationships to longterm outcomes and these are areas of future research. 13…”
Section: Polycystic Ovarian Morphologymentioning
confidence: 99%
“…In recent years, novel approaches and analytical assays have been used (Pankhurst et al, 2017;Wissing et al, 2019), which aim to determine whether the ratios of proAMH or AMH N,C in serum are altered in women with PCOS relative to women without PCOS, and to understand if different AMH-related isoforms can be used to predict PCOS. The results of those studies, however, are conflicting, either reporting differences in the mean proAMH-AMH N,C ratio in the PCOS group compared with the unaffected control group (Pankhurst et al, 2017) or reporting no differences in the relative distribution of the AMH isoforms between those groups (Wissing et al, 2019). We hypothesized that part of the discrepancies could be due to the heterogeneity of the disorder, and that stratifying women with and without PCOS based on their metabolic phenotype (body mass index [BMI]) could better help to pin-point eventual differences in AMH cleavage.…”
Section: Introductionmentioning
confidence: 99%